Factors Influencing the Utilization of Antenatal Care, Institutional Delivery, and Postnatal Care Services Among Women in Bangladesh - Chowdhury, Akibul Islam; Habib, Mohammad Asadul; Rahman, Tanjina (UI Scholars Hub, 2022)
Background: In Bangladesh, the utilization of maternal health services is low, which triggers pregnancy-related complications and maternal deaths. The current community-based cross-sectional study aims to evaluate the factors associated with antenatal care (ANC), institutional delivery, and postnatal care (PNC) service utilization among women in selected areas of Southwest Dhaka, Bangladesh. Methods: The study was carried out among 391 mothers from rural and urban areas. Data were collected using a standard questionnaire. Univariate and multivariate analyses were performed to identify the significant determinants associated with maternity care service utilization. Results: Result shows that approximately 65%, 71%, and 72% of women utilized the recommended ANC, institutional delivery, and PNC, respectively. The utilization of ANC was associated with residence type and women’s education, whereas the utilization of institutional delivery and PNC was associated with residence type, women’s education, husband’s education and employment status, family size, monthly family income, and received ANC. The use of ANC and healthy delivery facilities is another important predictor of PNC service utilization. Conclusions: Considering these findings, improved maternal health services, increased availability and affordability of services, counseling, and education during pregnancy are advocated throughout the country.